2022
DOI: 10.3991/ijim.v16i04.27103
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Attendance and Participation in Online Class During the COVID Pandemic: A Case Study

Abstract: COVID-19 pandemic has transformed the traditional education in all levels to be shifted to online classrooms. Monitoring student’s attendance and interaction during live online classes is a challenge for educators. During the lockdown, many factors influenced the participation and attendance to online class, which we will highlight them in this research. This research investigated the participation of students registered in course Introduction to Web Programming Lab at Hashemite University. Students' participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Building new intelligent and efficient frameworks is becoming easier with the features pro-vided by B5G, such as low latency, larger area coverage, higher data rate, and real-time communication [25]. Similarly, social media is a potentially good platform for disseminating important information during the pandemic [26]. Significantly, during the pandemic outbreak, the need for rapid analysis, decision-making, and prediction of future trends become paramount [25] [27].…”
Section: Cluster 1: Technologymentioning
confidence: 99%
“…Building new intelligent and efficient frameworks is becoming easier with the features pro-vided by B5G, such as low latency, larger area coverage, higher data rate, and real-time communication [25]. Similarly, social media is a potentially good platform for disseminating important information during the pandemic [26]. Significantly, during the pandemic outbreak, the need for rapid analysis, decision-making, and prediction of future trends become paramount [25] [27].…”
Section: Cluster 1: Technologymentioning
confidence: 99%
“…Pivetta [24] brought together several studies that highlight a few problematic behaviors that may be associated with excessive smartphone use; including symptoms related to addiction, stress and sleep disturbances, financial problems, dangerous driving, or antisocial and prohibited use. Furthermore, the possibility of being constantly connected to the Internet has been found to increase the potentially unregulated and excessive use of smartphones for entertainment purposes such as social networking, video games and gambling or streaming services [28].…”
Section: Irresponsible or Unintended Habits Causing Wastementioning
confidence: 99%
“…Meaning Learners hardly develop own initiative of positive development of ideas obtain from the discussion and sharing of insights. Qutishat, et al (2022) Based on attendance, class engagement, assignment delivery, and use of online learning tools, students' initiative was evaluated. Results showed that online education was successfully implemented, and students grasped the material content, according to a poll of students' course learning outcomes (CLOs).…”
Section: Statementsmentioning
confidence: 99%